Keragaman Pepaya (Carica papaya L.) di Kotamadya Pontianak Berdasarkan Karakter Morfologi - Wardoyo, Elvi R.P.; Oktavia, Vivi; Turnip, Masnur (Jurusan Biologi FMIPA Universitas Cenderawasih, 2024)
Papaya (Carica papaya L.) is a plant that is widely cultivated in Indonesia. Pontianak City is one of the centers for the production of papaya cultivation, with a production of 12,593 tons in 2019. This study aims to determine the diversity and kinship of papaya in Pontianak City based on its morphological characters. The research was conducted from September to October 2021 in Pontianak City. A total of 32 individuals were sampled from six districts using the cruising method. Consanguinity was analyzed on 28 morphological characters using the UPGMA method with the NTSYS ver. 2.0. The results indicated that the 32 papaya accessions exhibited a similarity coefficient value of 0.35, which represents a 35% level of similarity. The papaya plants in Pontianak City exhibited a low level of similarity but a high level of diversity.